Assessing multiple approaches for modelling land-use conflict potential from participatory mapping data. (September 2017) - Karimi, Azadeh; Brown, Greg
Highlights: Evaluates methods for identifying land-use conflict from participatory spatial data. Methods using land-use preferences performed best across multiple land uses. Results were sensitive to the quantity of spatial data and participants. Operationalises confidence levels to assess inferential quality of results. Suggests prioritisation to areas with high potential conflict and high confidence. Abstract: Spatial social data collected through participatory mapping are increasingly used to assess social dimensions for land use planning and management. However, there has been limited research to evaluate alternative approaches to identify potential land-use conflict. Using data from Queensland, Australia, we applied multiple approaches (land-use preferences, weighted preferences, combined place values and land-use preferences, and value compatibility scoring to identify land-use conflict potential and to assess these methods for four different land uses (residential development, tourism development, mining, and conservation). The performance of these approaches were evaluated using selected reference sites in the study area to determine which spatial attributes and methods were most predictive of conflict potential. Weighted preferences, and combined place values and land-use preferences were most effective for all land use types. The conflict mapping results for mining and conservation were sensitive to the number of place value and land-use preference points available for analysis and the number of individuals participating in the mapping process. To determine the inferential quality of conflict mapping results, we operationalised confidence levels based on the number of unique participants that mapped preferences in a given location. Overall, the highest confidence in mapped results was observed for tourism development, followed by mining, conservation, and residential development. Confidence levels varied across the study area and by reference sites. The findings of this study increase the external validity of preference-based conflict mapping methods while demonstrating a means to assess the inferential quality of conflict mapping results. The generation of confidence levels can assist in the prioritization and allocation of planning resources to places with both high conflict potential and high confidence.